Bioactivity Screening of Endophytic Fungi Isolated from Nypa fruticans Leaves: Antioxidant, Antibacterial, and Cytotoxic Evaluations - Dwinatrana, Khiky; Gefi Dwi Hermanto; Intan Lestari; Ananda Ogesta; Helmice Afriyeni; Rustini (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2026)
Background: Nypa fruticans is a mangrove palm known to harbor diverse endophytic microorganisms with potential bioactivity. However, studies on the biological properties of endophytic fungi are scarce. Objective: This study aimed to evaluate the antioxidant, antibacterial, and cytotoxic activities of endophytic fungi isolated from N. fruticans leaves and to characterize their secondary metabolite profiles. Methods: Eight fungal isolates (NF1–NF8) were obtained and screened for antioxidant activity using the DPPH radical-scavenging method, antibacterial activity against Staphylococcus aureus and Escherichia coli using the disc diffusion method, and cytotoxicity using the Artemia salina lethality test. The most active isolates were further analyzed using thin-layer chromatography (TLC) and phytochemical tests. Results: The isolates exhibited varying bioactivities, with NF5 showing antioxidant potential (IC₅₀ = 152.6 µg/mL) and NF7 showing the strongest antibacterial (19.1 ± 0.25 mm inhibition zone) and cytotoxic activities (LC₅₀ = 198.81 µg/mL). TLC and reagent detection confirmed the presence of phenolic compounds in NF5 and terpenoid compounds in NF7, corresponding to their biological profiles. Conclusion: The endophytic fungi from N. fruticans leaves exhibited significant antioxidant, antibacterial, and cytotoxic activities, indicating their potential as novel sources of natural bioactive metabolites, particularly in palm-associated fungal communities.